Dual drug targeting to kill colon cancers. (17th March 2022) - Corona, Silvia Paola; Walker, Francesca; Weinstock, Janet; Lessene, Guillaume; Faux, Maree; Burgess, Antony W.
Abstract: Introduction: Colorectal cancer (CRC) is driven by a small set of oncogenic and tumour suppressor mutations. However, different combinations of mutations often lead to poor tumour responses to individual anticancer drugs. We have investigated the antiproliferative and in vitro cytotoxic activity of pair‐wise combinations of inhibitors which target specific signalling pathways in colon cancer cells. Objectives: To target specific signaling pathways pairwise with inhibitors in order to kill colon cancer cells. Methods: The effects of different concentrations of two inhibitors on the proliferation and viability of colon cancer cell lines were measured using cell titre glow and cytotoxic assays in 2D and 3D cell micro‐cultures. One successful drug combination was used to treat a colon cancer cell line growing as a xenograft in nude mice. Results: Colon cancer cells in non‐adherent cultures were killed more effectively by combinations of pyrvinium pamoate (a Wnt pathway inhibitor) and ABT263 (a pro‐apoptotic Bcl‐2 family inhibitor) or Ly29004 (a PI3kinase inhibitor). However, in a mouse xenograft model, the formulation and toxicity of the ABT737/PP combination prevent the use of these drugs for treatment of tumours. Fortunately, oral analogues of PP (pyrvinium phosphate, PPh) and ABT737(ABT263) have equivalent activity and can be used for treatment of mice carrying SW620 colorectal cancer xenografts. The PPh/ABT263 induced SW620 tumour cell apoptosis and reduced the rate of SW620 tumour growth. Conclusion: By combining a Wnt signaling inhibitor (pyrvinium phosphate) and a pro‐survival inhibitor (ABT263) colon cancer cells can be killed. Combinations of Wnt signalling inhibitors with an inhibitor of the Bcl pro‐survival protein family should be considered for the treatment of patients with precancerous colon adenomas or advanced colorectal cancers with APC mutations. Abstract : Most colon cancer cells have a truncated tumor suppressor protein Apc. This mutation facilitates excess signaling through the Wnt pathway. The combination of a Wnt inhibitor (pyrvinium pamoate) with a pro‐apoptotic drug (ABT‐263) induces the killing of Apc defective colon cancer cells.